Predictors of Effectiveness of Glucagon-Like Peptide-1 Receptor Agonist Therapy in Patients with Type 2 Diabetes and Obesity - Alina Yu. Babenko; Daria A. Savitskaya; Yulia A. Kononova; Aleksandra Yu. Trofimova; Anna V. Simanenkova; Elena Yu. Vasilyeva; Evgeny V. Shlyakhto (Journal of Diabetes Research)
Rationale. It is well known that diabetes mellitus (DM) exacerbates the mechanisms underlying atherosclerosis. Currently, glucagon-like peptide-1 receptor agonists (aGLP-1) have one of the most prominent cardioprotective effects among the antidiabetic agents. However, the treatment with aGLP-1 is effective only in 50-70% of the cases. Taking into account the high cost of these medications, discovery of the predictors of optimal response to treatment is required. Purpose. To identify the predictors of the greater impact of aGLP-1 on HbA1c levels, weight reduction, and improvement in lipid profile. Methods. The study group consisted of 40 patients with type 2 DM (T2DM) and obesity who were treated with aGLP-1. The follow-up period was 24 weeks. Patients’ evaluation was conducted at baseline and after 24 weeks. In addition, it included the assessment of the hormones involved in glucose and lipid metabolism and appetite regulation. Results. Patients who have initially higher BMI (body mass index), glycemia, and triglycerides (TG) had better improvement in these parameters undergoing aGLP-1 treatment. In patients with a BMI loss≥5%, GLP-1 and fasting ghrelin levels were higher and ghrelin level in postnutritional status was lower. The HbA1c levels decreased more intensively in participants with higher GLP-1 levels. TG responders had lower baseline fasting glucose-dependent insulinotropic peptide (GIP) and postprandial ghrelin levels. Conclusion. The evaluation of the glycemic control, lipid profile, and GLP-1, GIP, and ghrelin levels are useable for estimating the expected efficacy of aGLP-1.